Role of Foliar Nutrition with Zinc and Boron on Some Growth Parameters of Chickpea Plant (Cicer arietinum L.). - Amel Gh. M. Al â€“Kazzaz (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
The experiment was carried out in the wooden canopy in the green garden of Biology Department , College of Education for Pure Science â€“ Ibn AL â€“Haitham, Baghdad University, during the growing season of 2012- 2013 , to study the influence of foliar application of three concentrations of zinc  (0,50,75)mg. L Â¯Â¹  with four concentrations of boron (0, 25, 50, 75) mg. LÂ¯Â¹ and their interactions on some growth parameters of vegetative part of chickpea plant. The experiment was designed according to Randomized Completely Block  Design(RCBD)with three replications, results indicated that:- 1- Foliar application of zinc  and boron caused a significant increase in the averaye of dry weight for the first harvest, No. of branches. plantÂ¯Â¹, No. of flowers . plantÂ¯Â¹ , the relative efficiency of fertilizer for the first harvest , the secondary productivity , the content of each nitrogen , phosphorus and calcium for the both harvests , percentage of protein for the both harvests and the content of total chlorophyll, compared with the control . 2- The interaction effect between the two elements was significant in the growth parameters and superiority of the treatment 75 mg . LÂ¯Â¹  zinc and 75 mg. LÂ¯Â¹ boron in giving the best value.